Co‐production and social innovation in street‐level employability services: Lessons from services with lone parents in Scotland. (30th October 2018) - Lindsay, Colin; Pearson, Sarah; Batty, Elaine; Cullen, Anne Marie; Eadson, Will
Abstract: The United Kingdom, as an exemplar liberal welfare state, has been characterized as in the vanguard of "work‐first" activation – deploying high levels of compulsion and standardized employability services that seek to move people from welfare to work as quickly as possible. However, despite the extension of welfare conditionality to excluded groups such as lone parents, government‐led, work‐first employability programmes have often proved ineffective at assisting the most vulnerable to escape poverty or even just to progress in the labour market. We argue that alternative approaches, defined by co‐production and social innovation, have the potential to be more successful. We draw on a study of local services targeting lone parents led by third sector–public sector partnerships in five localities in Scotland. Our research identifies a link between programme governance and management (defined by co‐governance and collaborative partnership‐working) and co‐produced street‐level services that deliver benefits in terms of social innovation and employability. We draw on 90 interviews with lone parents, and more than 100 interviews with delivery stakeholders and street‐level workers, to identify factors associated with positive social and employability outcomes. The article concludes by identifying potential lessons for the governance and delivery of future services targeting vulnerable groups.